Vocational Education in the Era of Big Data: Course Design and Optimization Strategy Based on Educational Technology - Wang, Yunan; Feng, Liang (International Journal of Interactive Mobile Technologies (iJIM), 2024)
In the era of big data, vocational education is confronted with the challenge of effectively utilizing students’ learning behavior data. With the advancement of information technology, the accumulation of students’ learning trajectories and behavior data presents new opportunities for the optimization of education and teaching. Currently, many studies focus on the analysis of short-term learning behaviors, while comprehensive consideration of both long- and short-term behaviors remains insufficient, limiting the precision of course design and resource recommendations. Therefore, the exploration of an optimization strategy that integrates students’ long- and short-term learning behaviors is urgently needed to enhance the effectiveness of vocational education. This study aims to propose a course design and optimization strategy based on educational technology, with a focus on integrating students’ long- and short-term learning behaviors, thereby presenting corresponding resource recommendation methods and course design plans. The study will provide more personalized and precise teaching solutions for vocational education, promoting the enhancement of educational quality.